Diurnal changes of blood pressure values (24 h blood pressures) in women with polycystic ovary syndrome - Grzechocińska, Barbara; Cyganek, Anna; Marianowski, Piotr (Menopause Review/Przegląd Menopauzalny, 2011)
Background: More attention is being paid lately to polycystic ovary syndrome (PCOS) not only in the aspect of fertility but also according to long-term metabolic and cardiovascular abnormalities. Observations of women with PCOS show that the occurrence of blood hypertension is more frequent after the menopause. There are few articles concerning the predictable symptoms of blood hypertension. It seems that twenty-four hour blood pressure monitoring and assessment of changes of diurnal rhythm could be useful in this group of patients. Aim of the study : The purpose of this study was to assess diurnal changes of blood pressure in women with polycystic ovary syndrome. Material and methods: 26 women with PCOS diagnosed according to Rotterdam consensus criteria and Androgen Excess Society (AES) criteria were included in our study. The mean age of the examined women was 29.5 years and the mean BMI (body mass index) was 24.7 kg/m 2 . The control group consisted of 12 age-matched women, without PCOS. Twenty-four hour Holter monitoring of ambulatory blood pressure was performed during normal daily activity in all patients. Halberg’s cosinor method was used to analyse daily biorhythm. Results: Results show the diurnal changes of systolic blood pressure in the preclinical phase in 30% and diastolic in 15% of PCOS women. In this group no physiological decrease of blood pressure at night time was observed.